Implementasi Problem Based Learning untuk Meningkatkan Aktivitas dan Hasil Belajar Mahasiswa - Rizka Novi Irmaningrum; Oriza Zativalen; Linaria Arafatul Ilmi Uswatun Khasanah (Elementa: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The purpose of this study was to improve student learning outcomes in the basics of education courses. This type of research is classroom action research. Which is carried out in 2 cycles consisting of planning, observation, evaluation, and reflection stages. The sample in this study was the second semester students of PGSD Batch III, totaling 58 students. The research procedure used two cycles with the methods used in data collection, namely the test, observation, and documentation methods. Data were analyzed descriptively qualitatively. The results showed that the percentage for understanding the concept was indicated by learning outcomes, namely in the first cycle it reached 71.02% and in the second cycle it reached 89.98%. The final results of student learning outcomes are classified as very good criteria. The conclusion of this research is that the implementation of problem based learning with the discussion method can improve student learning outcomes.